Actin cytoskeletal dynamics in T lymphocyte activation and migration - Samstag, Yvonne; Eibert, Sybille M.; Klemke, Martin; Wabnitz, Guido H. (Journal of leukocyte biology, 2003)
Dynamic rearrangements of the actin cytoskeleton are crucial for the function of numerous cellular elements including T lymphocytes. They are required for migration of T lymphocytes through the body to scan for the presence of antigens, as well as for the formation and stabilization of the immunological synapse at the interface between antigen-presenting cells and T lymphocytes. Supramolecular activation clusters within the immunological synapse play an important role for the initiation of T cell responses and for the execution of T cell effector functions. In addition to the T cell receptor/CD3 induced actin nucleation via Wasp/Arp2/3-activation, signals through accessory receptors of the T cell (i.e., costimulation) regulate actin cytoskeletal dynamics. In this regard, the actin-binding proteins cofilin and L-plastin represent prominent candidates linking accessory receptor stimulation to the rearrangement of the actin cytoskeleton. Cofilin enhances actin polymerization via its actin-severing activity, and as a long-lasting effect, cofilin generates novel actin monomers through F-actin depolymerization. L-plastin stabilizes actin filament structures by means of its actin-bundling activity.